Signatures and Mechanism Analysis of Converter-Grid Subsynchronous Oscillations - Askarov A. B. Alisher Bakhramzhonovich; Bay Yu. D. Yuly Dmitrievich; Ufa R. A. Ruslan Alexandrovich; Radko P. P. Pavel Pavlovich; Ilyushin P. V. Pavel Vladimirovich; Suvorov A. A. Aleksey Aleksandrovich (2024, 2024)
Title screen